Housing and Settlements in The Ujung Menteng Urban Village area - Khansyah, Rifqi (ARCHIHUMANUM, 2024)
This study aims to assess the housing and settlement dynamics within the Kelurahan Ujung Menteng area. Findings reveal a range of challenges impeding housing and settlement progress, encompassing inadequate access to fundamental services like clean water, sanitation, and road infrastructure. Moreover, socio-economic factors significantly influence the community's quality of life. In light of these findings, the research advocates several strategic initiatives to enhance housing and settlement conditions in Kelurahan Ujung Menteng. These include enhancing the accessibility of essential infrastructure, implementing affordable housing schemes, and fostering community empowerment in decision-making processes concerning area development.